Effects of Static and Dynamical Disturbance Forces on the Performance of a Wire Driven Flexible Robot - Tahmasebi, Mona; Gohari, Mohammad; Zolfagharian, Ali; Zare, Mohammad Reza; Pak, Abbas (Peneliti Teknologi Teknik Indonesia, 2025)
Robot requests are increased by recent development of IoT, telemetry and human requirements in uninteresting or precision jobs such as surgery, industrial inspections or crops harvesting. Numerous robots are industrialized by researchers for various tasks. Flexible robots are developed based on declared requests since they can adapt their geometry to the working circumstances. Existing study presents a wire driven flexible robot enthused of animal organs such as octopus tentacles or elephant`s trunk. It can move in planar and space based on assembly of that. Primarily, a kinematic model founded to estimate end effector location, formerly a dynamic model established to compute essential tension of tendon based on bending beam theory. Moreover, effects of static and dynamical load applied on the WDFR are studied as external disturbances. A test rig is fabricated to assess attained models. The results demonstrate close convergence between tests outcomes and outputs of models. Accordingly, dynamic and kinematic models can be operated in design of controller in coming works.